A metal particle-loaded self-supporting electrode material and its preparation method and application
By using metal particles to load self-support electrode materials in zinc bromine batteries, metal particles are deposited using functionalized aqueous solution and three-electrode electrochemical deposition technology to form a composite structure of transition metal nanoparticles and carbonized wood chips, the problems of high solubility of polybrominated ion products in zinc bromine batteries and insufficient electrocatalytic activity of Br2/Br-redox reaction in zinc bromine batteries are solved, and high-efficiency energy conversion and storage are achieved, and the overall performance of the battery is improved.
Patent Information
- Application Number
- CN202411918244.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The polybrominated ion products produced by zinc-brominated batteries have high solubility, resulting in severe shuttle effect, and insufficient electrocatalytic activity of Br2/Br-redox reaction, resulting in large energy loss.
The metal particles are loaded with self-supporting electrode material, and the metal salt is dissolved in a functionalized aqueous solution, and metal particles are deposited on the carbonized wood chips by using three-electrode electrochemical deposition technology, and pyrolytic treatment is carried out in a hydrogen-argon mixed atmosphere to form a composite structure of transition metal nanoparticles and carbonized wood chips.
The average Coulomb efficiency, voltage efficiency and energy efficiency of zinc-bromine batteries are improved, ensuring the efficient energy conversion and storage of the battery, and improving overall performance.
Smart Images

Figure CN119361725B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery electrodes, and in particular relates to a metal particle-loaded self-supporting electrode material and a preparation method and application thereof. Background Art
[0002] Zinc-bromine batteries have attracted extensive attention in the field of energy storage technology due to their advantages such as low cost, high safety, high energy density and wide operating temperature. However, the polybromine ion products produced by the bromide ions on the electrode side during the charging process have high solubility in the electrolyte. The dissolved polybromine products quickly transfer to the surface of the zinc metal negative electrode and react directly with zinc, causing a serious shuttle effect. In addition, Br2 / Br - The intrinsic kinetics of redox reactions are sluggish, resulting in huge energy losses.
[0003] A large number of studies often use porous materials such as graphite felt or carbon felt as electrode support substrates, taking advantage of their high conductivity and high specific surface area to provide a large reaction interface for the redox reaction of bromine. However, due to the disordered pores of porous electrodes, the electrolyte flow resistance is large, the electrode reaction is controlled by diffusion mass transfer, and the limiting current density is proportional to the electrode thickness. Using ordered porous carbon materials as electrode substrates can regulate the electrolyte flow path and is expected to quickly and fully utilize the reaction active sites.
[0004] In addition, Br2 / Br - The electrocatalytic activity of redox reactions is considered to be an important aspect of improving reaction kinetics, reducing battery electrochemical polarization, and inhibiting the shuttle effect. Compared with carbon, transition metal nanoparticles have stronger chemical interactions with bromine and stronger catalytic activity, and can adsorb and fix dissolved bromine while catalyzing bromine conversion. Therefore, how to better composite transition metal nanoparticles with ordered pore carbon materials to provide more and more reliable active sites for bromine electrochemical reactions, so as to achieve high energy efficiency and fast charge and discharge response of zinc-bromine batteries, deserves further study. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a metal particle-loaded self-supporting electrode material and a preparation method and application thereof, which ensure that the transition metal particles and the carbonized wood chips are better compounded together, provide more and more reliable active sites for the bromine electrochemical reaction, and thus improve the overall performance of the zinc-bromine battery.
[0006] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a method for preparing a metal particle-loaded self-supporting electrode material, comprising the following steps:
[0007] S1, cutting the beech wood into pieces with a thickness of 5-7 mm along the vertical growth direction, and then calcining the pieces to obtain carbonized wood pieces;
[0008] S2, dissolving a metal salt in a functionalized aqueous solution, wherein the concentration of the metal salt is 0.03-0.05 M, to obtain an immersion solution; the functionalized aqueous solution comprises dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water, and the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1: (0.7-0.9): (0.3-0.5): (60-65);
[0009] S3, using a three-electrode electrochemical deposition technique, taking the carbonized wood chip obtained in S1 as a working electrode, immersing it in the soaking solution obtained in S2, electro-depositing a metal precursor, and then washing and drying to obtain a metal-loaded wood chip;
[0010] S4. Pyrolyze the metal-loaded wood chips obtained in S3 in a hydrogen-argon mixed atmosphere, then cool to room temperature, wash, and dry to obtain a metal particle-loaded self-supporting electrode material.
[0011] Furthermore, in S1, the specific operation of the calcination treatment is: calcination temperature 850-950° C., calcination time 1.5-2.5 h.
[0012] Furthermore, in S2, the metal salt includes any one of manganese chloride, ferric chloride, cobalt chloride, nickel chloride and cupric chloride.
[0013] Furthermore, in S2, the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1:0.8:0.4:63.
[0014] Furthermore, the preparation method of the functionalized aqueous solution is as follows:
[0015] A1. Weigh dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water according to the mass ratio;
[0016] A2, add dodecyltrimethylammonium chloride to 1 / 2 mass of water, stir until completely dissolved, then add sodium pyrophosphate, continue stirring until completely dissolved, then add polyvinylpyrrolidone, continue stirring until completely dissolved, to obtain a mixed solution;
[0017] A3, adding the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, stirring to mix well, to obtain the functionalized aqueous solution.
[0018] Furthermore, in S3, the deposition voltage is -1.8~-2.4V, and the deposition time is 10~15min.
[0019] Furthermore, in S4, the specific operation of the pyrolysis treatment is: pyrolysis temperature 350-450° C., pyrolysis time 3-6 h.
[0020] Furthermore, in S3 and S4, ethanol and deionized water were used for alternate washing for multiple times, and then dried at room temperature.
[0021] In a second aspect, the present invention provides a metal particle-loaded self-supporting electrode material, which is prepared by the above-mentioned preparation method.
[0022] In a third aspect, the present invention provides an application of a metal particle-loaded self-supporting electrode material, wherein the metal particle-loaded self-supporting electrode material is prepared by the above-mentioned preparation method, and the metal particle-loaded self-supporting electrode material is used in a zinc-bromine battery.
[0023] This application has the following beneficial effects:
[0024] 1. The present invention uses dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water to prepare a functionalized aqueous solution, then dissolves a metal salt in the functionalized aqueous solution to obtain a soaking solution, and uses the soaking solution to perform an electrodeposition treatment on carbonized wood chips to obtain a metal particle-loaded self-supporting electrode material; the electrode material is applied to a zinc-bromine battery, and the average coulomb efficiency (CE) of the battery is as high as 95.1% or more; the voltage efficiency (VE) is as high as 85.7% or more; and the energy efficiency (EE) is as high as 81.9% or more; indicating that the electrode material prepared by the present invention has excellent electrochemical activity, can achieve efficient energy conversion and storage in the battery, and can ensure the excellent overall performance of the prepared battery.
[0025] 2. In the preparation of the functionalized aqueous solution of the present invention, the addition of polyvinyl pyrrolidone has good film-forming and protective properties, and can form a protective film on the surface of metal particles, effectively preventing the agglomeration and oxidation of metal particles, thereby having a positive impact on the electrodeposition effect of metal particles; on the other hand, excessive coverage of the film will lead to excessive reduction of the effective surface area participating in the reaction, thereby bringing negative effects.
[0026] The addition of dodecyltrimethylammonium chloride can not only help reduce the agglomeration between metal particles, increase their dispersion in the solution, and improve their uniformity of distribution on carbonized wood, thereby having a positive impact on the electrodeposition effect of metal particles; it can also reduce the surface tension of the solution, making the distribution of polyvinylpyrrolidone molecules in the solution more uniform, thereby reducing its excessive aggregation and continuous film formation on the surface of metal particles; the hydrophobic groups of dodecyltrimethylammonium chloride will also interact with polyvinylpyrrolidone molecules, change the arrangement of polyvinylpyrrolidone molecules, make the formed film discontinuous, thereby reducing the degree of coating on metal particles, that is, weakening the negative impact of polyvinylpyrrolidone.
[0027] The addition of sodium pyrophosphate can form a stable complex with metal ions, significantly improve the stability of metal ions in the soaking solution, and prevent them from prematurely depositing or forming precipitation. Through this adjustment, the uniformity and density of metal ions reduced from the soaking solution and deposited on the carbonized wood chips can be improved. At the same time, the formation of the complex can change the existence state and reaction activity of metal ions, affect the combination mode and degree of polyvinyl pyrrolidone and metal ions, make the coating process during film formation more complicated, and thus form a discontinuous film, that is, weaken the negative impact of polyvinyl pyrrolidone.
[0028] In summary, the dodecyltrimethylammonium chloride, sodium pyrophosphate and polyvinylpyrrolidone of the present invention work synergistically through their respective characteristics and interactions in the preparation of functionalized aqueous solutions, synergistically improve the electrochemical activity of the prepared electrode material, and ultimately synergistically improve the overall performance of the prepared battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 , a comparison trend chart of average coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) test data of the electrode materials prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 7 and applied to zinc-bromine batteries;;
[0030] Figure 2 , surface morphology of the electrode material obtained in Example 1 of the present invention;
[0031] Figure 3 , an enlarged view of the surface morphology of the electrode material obtained in Example 1 of the present invention;
[0032] Figure 4 , surface morphology of the electrode material obtained in comparative example 7 of the present invention. DETAILED DESCRIPTION
[0033] The present application is further described in detail below with reference to the embodiments.
[0034] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0035] Example 1: (1) A functionalized aqueous solution is prepared as follows:
[0036] A1. Weigh dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water according to the mass ratio; the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1:0.8:0.4:63.
[0037] A2. Add dodecyltrimethylammonium chloride to 1 / 2 of the mass of water, stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add sodium pyrophosphate, continue to stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add polyvinylpyrrolidone, stir at a stirring speed of 220 r / min for 15 min until it is completely dissolved to obtain a mixed solution.
[0038] A3. Add the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0039] (2) A method for preparing a metal particle-loaded self-supporting electrode material, comprising the following steps:
[0040] S1. Cut the beech wood into slices with a thickness of 6 mm along the vertical growth direction, and then perform calcination treatment. The specific operation of the calcination treatment is: calcination temperature 900° C., calcination time 2 h, to obtain carbonized wood chips.
[0041] S2. Add cobalt chloride to the functionalized aqueous solution, and stir at a stirring speed of 280 r / min for 30 minutes to obtain an immersion solution. The concentration of cobalt chloride in the immersion solution is 0.04 M.
[0042] S3, using three-electrode electrochemical deposition technology, the carbonized wood chip obtained in S1 is used as the working electrode, and it is immersed in the soaking solution obtained in S2 to electro-deposit the metal precursor. Specifically, the carbonized wood chip obtained in S1 is used as the working electrode, and the platinum sheet and Ag / AgCl are used as the counter electrode and the reference electrode respectively; in the soaking solution obtained in S2, the electrodeposition is carried out at a constant potential of -2.0Vvs.Ag / AgCl for 13 minutes; after the electrodeposition is completed, it is washed alternately with ethanol and deionized water twice, and dried at room temperature to obtain a metal-loaded wood chip.
[0043] S4, the metal-loaded wood chips obtained in S3 were heated to 400°C at a heating rate of 5°C / min in a hydrogen-argon mixed atmosphere, and maintained for 4 hours. After the pyrolysis reaction was completed, they were cooled to room temperature, washed twice with ethanol and deionized water alternately, and dried at room temperature to obtain a metal particle-loaded self-supporting electrode material. The electrode material was characterized, and its morphology is shown in the figure below. Figure 2 and Figure 3 shown.
[0044] Example 2: The difference between this example and Example 1 is that: (1) a functionalized aqueous solution is prepared, and the preparation method thereof is as follows:
[0045] A1. Weigh dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water according to the mass ratio; the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1:0.7:0.3:60.
[0046] A2. Add dodecyltrimethylammonium chloride to 1 / 2 of the mass of water, stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add sodium pyrophosphate, continue to stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add polyvinylpyrrolidone, stir at a stirring speed of 220 r / min for 15 min until it is completely dissolved to obtain a mixed solution.
[0047] A3. Add the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0048] Example 3: The difference between this example and Example 1 is that: (1) a functionalized aqueous solution is prepared, and the preparation method thereof is as follows:
[0049] A1. Weigh dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water according to the mass ratio; the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1:0.9:0.5:65.
[0050] A2. Add dodecyltrimethylammonium chloride to 1 / 2 of the mass of water, stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add sodium pyrophosphate, continue to stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add polyvinylpyrrolidone, stir at a stirring speed of 220 r / min for 15 min until it is completely dissolved to obtain a mixed solution.
[0051] A3. Add the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0052] Example 4: The difference between this example and Example 1 is that: (2) A method for preparing a metal particle-supported self-supporting electrode material comprises the following steps:
[0053] S1. Cut the beech wood into slices with a thickness of 5 mm along the vertical growth direction, and then perform calcination treatment. The specific operation of the calcination treatment is: calcination temperature 850° C., calcination time 2.5 h, to obtain carbonized wood chips.
[0054] S2. Add manganese chloride to the functionalized aqueous solution, and stir at a stirring speed of 280 r / min for 30 minutes to obtain a soaking solution. The concentration of manganese chloride in the soaking solution is 0.03M.
[0055] S3, using three-electrode electrochemical deposition technology, the carbonized wood chip obtained in S1 is used as the working electrode, and it is immersed in the soaking solution obtained in S2 to electro-deposit the metal precursor. Specifically, the carbonized wood chip obtained in S1 is used as the working electrode, and the platinum sheet and Ag / AgCl are used as the counter electrode and the reference electrode respectively; in the soaking solution obtained in S2, the electrodeposition is carried out at a constant potential of -1.8Vvs.Ag / AgCl for 15 minutes; after the electrodeposition is completed, it is washed alternately with ethanol and deionized water twice, and dried at room temperature to obtain a metal-loaded wood chip.
[0056] S4. The metal-loaded wood chips obtained in S3 are heated to 350°C at a heating rate of 5°C / min in a hydrogen-argon mixed atmosphere and maintained for 6 hours. After the pyrolysis reaction is completed, they are cooled to room temperature, washed twice with ethanol and deionized water alternately, and dried at room temperature to obtain a metal particle-loaded self-supporting electrode material.
[0057] Example 5: The difference between this example and Example 1 is that: (2) A method for preparing a metal particle-loaded self-supporting electrode material comprises the following steps:
[0058] S1. Cut the beech wood into slices with a thickness of 7 mm along the vertical growth direction, and then perform calcination treatment. The specific operation of the calcination treatment is: calcination temperature 950° C., calcination time 1.5 h, to obtain carbonized wood chips.
[0059] S2. Add cobalt chloride to the functionalized aqueous solution, and stir at a stirring speed of 280 r / min for 30 minutes to obtain an immersion solution. The concentration of cobalt chloride in the immersion solution is 0.05 M.
[0060] S3, using three-electrode electrochemical deposition technology, the carbonized wood chip obtained in S1 is used as the working electrode, and it is immersed in the soaking solution obtained in S2 to electro-deposit the metal precursor. Specifically, the carbonized wood chip obtained in S1 is used as the working electrode, and the platinum sheet and Ag / AgCl are used as the counter electrode and the reference electrode respectively; in the soaking solution obtained in S2, the electrodeposition is carried out at a constant potential of -2.2Vvs.Ag / AgCl for 10 minutes; after the electrodeposition is completed, it is washed alternately with ethanol and deionized water twice, and dried at room temperature to obtain a metal-loaded wood chip.
[0061] S4. The metal-loaded wood chips obtained in S3 are heated to 450°C at a heating rate of 5°C / min in a hydrogen-argon mixed atmosphere and maintained for 3 hours. After the pyrolysis reaction is completed, they are cooled to room temperature, washed alternately with ethanol and deionized water twice, and dried at room temperature to obtain a metal particle-loaded self-supporting electrode material.
[0062] Comparative Example 1: The difference between this comparative example and Example 1 is that the functionalized aqueous solution is replaced by water.
[0063] Specifically, a method for preparing a metal particle-loaded self-supporting electrode material comprises the following steps:
[0064] S1. Cut the beech wood into slices with a thickness of 6 mm along the vertical growth direction, and then perform calcination treatment. The specific operation of the calcination treatment is: calcination temperature 900° C., calcination time 2 h, to obtain carbonized wood chips.
[0065] S2. Add cobalt chloride into water, and stir at a stirring speed of 280 r / min for 30 min to obtain a soaking solution. The concentration of cobalt chloride in the soaking solution is 0.04 M.
[0066] S3, using three-electrode electrochemical deposition technology, the carbonized wood chip obtained in S1 is used as the working electrode, and it is immersed in the soaking solution obtained in S2 to electro-deposit the metal precursor. Specifically, the carbonized wood chip obtained in S1 is used as the working electrode, and the platinum sheet and Ag / AgCl are used as the counter electrode and the reference electrode respectively; in the soaking solution obtained in S2, the electrodeposition is carried out at a constant potential of -2.0Vvs.Ag / AgCl for 13 minutes; after the electrodeposition is completed, it is washed alternately with ethanol and deionized water twice, and dried at room temperature to obtain a metal-loaded wood chip.
[0067] S4. The metal-loaded wood chips obtained in S3 are heated to 400°C at a heating rate of 5°C / min in a hydrogen-argon mixed atmosphere and maintained for 4 hours. After the pyrolysis reaction is completed, they are cooled to room temperature, washed alternately with ethanol and deionized water twice, and dried at room temperature to obtain a metal particle-loaded self-supporting electrode material.
[0068] Comparative Example 2: The difference between this comparative example and Example 1 is that in the preparation of the functionalized aqueous solution, dodecyltrimethylammonium chloride and sodium pyrophosphate are deleted.
[0069] Specifically, a functionalized aqueous solution is prepared, and the preparation method thereof is as follows:
[0070] A1. Weigh polyvinyl pyrrolidone and water according to the mass ratio; the mass ratio of polyvinyl pyrrolidone to water is 0.4:63.
[0071] A2. Add polyvinyl pyrrolidone to 1 / 2 the mass of water and stir at a constant speed of 220 r / min for 15 min until it is completely dissolved to obtain a solution.
[0072] A3. Add the remaining 1 / 2 of the mass of water into the solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0073] Comparative Example 3: The difference between this comparative example and Example 1 is that dodecyltrimethylammonium chloride is deleted in the preparation of the functionalized aqueous solution.
[0074] Specifically, a functionalized aqueous solution is prepared, and the preparation method thereof is as follows:
[0075] A1. Weigh sodium pyrophosphate, polyvinyl pyrrolidone and water according to the mass ratio; the mass ratio of sodium pyrophosphate, polyvinyl pyrrolidone and water is 0.8:0.4:63.
[0076] A2. Add sodium pyrophosphate to 1 / 2 of the mass of water, stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add polyvinyl pyrrolidone, stir at a stirring speed of 220 r / min for 15 min until it is completely dissolved to obtain a mixed solution.
[0077] A3. Add the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0078] Comparative Example 4: The difference between this comparative example and Example 1 is that sodium pyrophosphate is deleted in the preparation of the functionalized aqueous solution.
[0079] Specifically, a functionalized aqueous solution is prepared, and the preparation method thereof is as follows:
[0080] A1. Weigh dodecyltrimethylammonium chloride, polyvinylpyrrolidone and water according to the mass ratio; the mass ratio of dodecyltrimethylammonium chloride, polyvinylpyrrolidone and water is 1:0.4:63.
[0081] A2. Add dodecyltrimethylammonium chloride to 1 / 2 of the mass of water, stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add polyvinylpyrrolidone, stir at a stirring speed of 220 r / min for 15 min until it is completely dissolved to obtain a mixed solution.
[0082] A3. Add the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0083] Comparative Example 5: The difference between this comparative example and Example 1 is that polyvinyl pyrrolidone is deleted in the preparation of the functionalized aqueous solution.
[0084] Specifically, a functionalized aqueous solution is prepared, and the preparation method thereof is as follows:
[0085] A1. Weigh dodecyltrimethylammonium chloride, sodium pyrophosphate and water according to the mass ratio; the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate and water is 1:0.8:63.
[0086] A2. Add dodecyltrimethylammonium chloride to 1 / 2 of the mass of water, stir at a stirring speed of 220 r / min for 10 min until it is completely dissolved; then add sodium pyrophosphate, continue stirring at a stirring speed of 220 r / min for 10 min until it is completely dissolved to obtain a mixed solution.
[0087] A3. Add the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, and continue stirring at a stirring speed of 220 r / min for 10 minutes to mix well, thereby obtaining a functionalized aqueous solution.
[0088] Comparative Example 6: The difference between this comparative example and Example 1 is that the carbonized wood chips are directly used as electrode materials.
[0089] Specifically, the preparation method of the carbonized wood chips is: cutting beech wood into slices with a thickness of 6 mm along the vertical growth direction, and then calcining the slices. The specific operation of the calcination treatment is: calcination temperature 900° C., calcination time 2 hours, to obtain carbonized wood chips.
[0090] Comparative Example 7: The difference between this comparative example and Example 1 is that a commercial carbon felt material with a thickness of 6 mm is placed at 60°C and dried for 12 hours before being directly used as an electrode material. The electrode material is characterized, and its morphology is as follows Figure 4 shown.
[0091] Test example: Test object: Electrodes were prepared according to Example 1 to Example 5 and Comparative Example 1 to Comparative Example 7.
[0092] Test items and methods: Each test object was applied to zinc-bromine flow battery to test efficiency performance. Test conditions: the electrolyte composition was 2.5 mol / L zinc bromide + 3 mol / L potassium chloride + 0.8 mol / L 1-methyl-1-ethylpyrrolidine bromide, the diaphragm was a microporous polyolefin diaphragm, and the charge and discharge current density was 20 mA / cm 2 , the charging SOC is 50%, and the discharge cut-off voltage is 0.6 V. The performance test data of the battery average coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) are shown in Table 1.
[0093] Among them, the average coulomb efficiency (CE) = (the amount of charge released during discharge / the amount of charge input during charging) × 100%. It is an important indicator to measure the efficiency of charge transfer during battery charging and discharging, and directly reflects the energy loss and side reaction degree of the battery during the charge and discharge cycle. High coulomb efficiency means that the battery has less charge loss during charging and discharging, and the battery efficiency is higher.
[0094] Voltage efficiency (VE) = (operating voltage of the battery during discharge / theoretical voltage) × 100%. It reflects the voltage maintenance capability of the battery in actual use, that is, the degree to which the battery voltage decreases during discharge. High voltage efficiency means that the battery voltage drops less during discharge and the battery performance is better.
[0095] Energy efficiency (EE) = (released energy / stored energy) × 100%. It describes the number of transmission bits that can be obtained when the system consumes unit energy, and represents the efficiency of the system's use of energy resources. The higher the EE, the more transmission bits the system obtains when it consumes unit energy, which means that the system has a higher efficiency in using energy resources. For batteries, EE reflects the energy conversion efficiency of the battery in actual use.
[0096] Table 1. Test data of the experimental example
[0097]
[0098] Result analysis: Analyze Example 1-Example 5 and combine the data in Table 1 and Figure 1 It can be seen that the electrode material prepared by the present invention is applied to zinc-bromine batteries, and the average coulombic efficiency (CE) of the battery is as high as over 95.1%; the voltage efficiency (VE) is as high as over 85.7%; and the energy efficiency (EE) is as high as over 81.9%, indicating that the electrode material prepared by the present invention has excellent electrochemical activity, can realize efficient energy conversion and storage in the battery, and can ensure the excellent overall performance of the prepared battery.
[0099] Analyze Example 1 and Comparative Examples 1-7 and combine the data in Table 1 and Figure 1 By comparing Comparative Example 1 and Comparative Example 2, compared with Comparative Example 1, polyvinyl pyrrolidone was added to the immersion solution used for electroplating in Comparative Example 2. As a result, when the electrode material was used in a zinc-bromine battery, the average coulomb efficiency (CE) test data of the battery decreased from 94.0% to 92.1%, the voltage efficiency (VE) test data decreased from 84.7% to 83.3%, and the energy efficiency (EE) test data decreased from 81.3% to 79.2%, indicating that the addition of polyvinyl pyrrolidone alone would lead to a decrease in the electrochemical activity of the electrode material, thereby reducing the overall performance of the battery finally obtained.
[0100] This is because when polyvinyl pyrrolidone is used alone, as a non-conductive polymer material, it will occupy or cover some active sites on the surface of metal particles due to film formation, resulting in a reduction in the effective surface area involved in the reaction, thereby affecting the electrochemical activity of the electrode material; its coverage on the surface of metal particles will also hinder the transmission of electrons, resulting in an increase in the internal resistance of the entire electrode system, affecting the electrical performance.
[0101] By comparing Comparative Example 1 and Comparative Example 5, it can be seen that compared with Comparative Example 1, dodecyltrimethylammonium chloride and sodium pyrophosphate are added to the immersion solution used for electroplating in Comparative Example 5. As a result, when the electrode material is used in a zinc-bromine battery, the average coulomb efficiency (CE) test data of the battery is increased from 94.0% to 94.9%, the voltage efficiency (VE) test data is increased from 84.7% to 85.5%, and the energy efficiency (EE) test data is increased from 81.3% to 81.7%; This shows that the addition of dodecyltrimethylammonium chloride and sodium pyrophosphate can improve the electrochemical activity of the prepared electrode material, thereby improving the overall performance of the final battery.
[0102] Combined with Example 1 for comparison, compared with Comparative Example 1, dodecyl trimethyl ammonium chloride, sodium pyrophosphate and polyvinyl pyrrolidone were added to the immersion solution used for electroplating in Example 1. As a result, when the electrode material was applied to the zinc-bromine battery, the average coulomb efficiency (CE) test data of the battery increased from 94.0% to 95.7%, the voltage efficiency (VE) test data increased from 84.7% to 86.3%, and the energy efficiency (EE) test data increased from 81.3% to 82.6%; and the three groups of test data of Example 1 were all greater than those of Comparative Example 5, indicating that when dodecyl trimethyl ammonium chloride and sodium pyrophosphate were present, the addition of polyvinyl pyrrolidone could further improve the electrochemical activity of the electrode material obtained, and further improve the overall performance of the battery obtained in the end. It shows that there is a synergistic effect between dodecyl trimethyl ammonium chloride, sodium pyrophosphate and polyvinyl pyrrolidone, which can synergistically improve the electrochemical activity of the electrode material obtained, and synergistically improve the overall performance of the battery obtained in the end.
[0103] In addition, by comparing Comparative Examples 2, 3 and 4, it can be seen that when polyvinyl pyrrolidone is present in the immersion solution used for electroplating, the addition of sodium pyrophosphate and dodecyltrimethylammonium chloride can respectively improve the electrochemical activity of the obtained electrode material, thereby improving the overall performance of the final battery.
[0104] Analyze Example 1 and Comparative Example 6 and combine the data in Table 1 and Figure 1 It can be seen that the electrochemical activity of the electrode material prepared by the present invention is better than that of the carbonized wood chip electrode material.
[0105] Analyze Example 1 and Comparative Example 7 and combine the data in Table 1 and Figure 1 It can be seen that the electrochemical activity of the electrode material prepared by the present invention is significantly better than that of the carbon felt electrode material.
[0106] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0107] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a metal particle-loaded self-supporting electrode material, characterized in that: The steps include: S1, cutting the beech wood into pieces with a thickness of 5-7 mm along the vertical growth direction, and then calcining the pieces to obtain carbonized wood pieces; S2, dissolving a metal salt in a functionalized aqueous solution, wherein the concentration of the metal salt is 0.03-0.05M, to obtain an immersion solution; the functionalized aqueous solution comprises dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water, and the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1:(0.7-0.9):(0.3-0.5):(60-65); the metal salt comprises any one of manganese chloride, ferric chloride, cobalt chloride, nickel chloride and copper chloride; S3, using a three-electrode electrochemical deposition technique, taking the carbonized wood chip obtained in S1 as a working electrode, immersing it in the soaking solution obtained in S2, electro-depositing a metal precursor, and then washing and drying to obtain a metal-loaded wood chip; S4. Pyrolyze the metal-loaded wood chips obtained in S3 in a hydrogen-argon mixed atmosphere, then cool to room temperature, wash, and dry to obtain a metal particle-loaded self-supporting electrode material.
2. The method for preparing a metal particle-supported self-supporting electrode material according to claim 1, characterized in that: In S1, the specific operation of the calcination treatment is: calcination temperature 850-950° C., calcination time 1.5-2.5 h.
3. The method for preparing a metal particle-supported self-supporting electrode material according to claim 1, characterized in that: In S2, the mass ratio of dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water is 1:0.8:0.4:
63.
4. The method for preparing a metal particle-supported self-supporting electrode material according to claim 1 or 3, characterized in that: The preparation method of the functionalized aqueous solution is as follows: A1. Weigh dodecyltrimethylammonium chloride, sodium pyrophosphate, polyvinylpyrrolidone and water according to the mass ratio; A2, add dodecyltrimethylammonium chloride to 1 / 2 mass of water, stir until completely dissolved, then add sodium pyrophosphate, continue stirring until completely dissolved, then add polyvinylpyrrolidone, continue stirring until completely dissolved, to obtain a mixed solution; A3, adding the remaining 1 / 2 of the mass of water into the mixed solution obtained in A2, stirring to mix well, to obtain the functionalized aqueous solution.
5. The method for preparing a metal particle-supported self-supporting electrode material according to claim 1, characterized in that: In S3, the deposition voltage is -1.8~-2.4V, and the deposition time is 10~15min.
6. The method for preparing a metal particle-supported self-supporting electrode material according to claim 1, characterized in that: In S4, the specific operation of the pyrolysis treatment is: pyrolysis temperature 350-450° C., pyrolysis time 3-6 h.
7. The method for preparing a metal particle-supported self-supporting electrode material according to claim 1, characterized in that: In S3 and S4, ethanol and deionized water were used for alternate washing multiple times, and then dried at room temperature.
8. A metal particle-supported self-supporting electrode material, characterized in that: The method is prepared according to any one of claims 1 to 7.
9. An application of a metal particle-loaded self-supporting electrode material, characterized in that: The metal particle-loaded self-supporting electrode material is prepared by the preparation method according to any one of claims 1 to 7, and the metal particle-loaded self-supporting electrode material is used in a zinc-bromine battery.
Citation Information
Patent Citations
Electrodeposition method for preparing transition metal nano-catalyst and application thereof in electrocatalytic CO2 reduction
CN112647099A
Preparation method of flexible self-supporting electrode material
CN114512352A